An electron paramagnetic resonance study of proton induced damage in plastic scintillators for the ATLAS detector - Pelwan, Chad Dean (My University, 2017)
Plastic scintillators, situated in the Tile Calorimeter (TileCal) of the ATLAS detector at the Large Hadron Collider (LHC), play an integral part in the detection of diﬀractive, energetic hadronic particles that result from high energy proton-proton collisions. As these particles traversetheplastic, theresultantdecayofthepolymerbaseemitsluminescentlightwhichacts as a signature of this interaction. However, the deleterious radiation environment in which the plastics are situated ultimately degrade the plastic through the formation of free radicals which initiate chemical reactions and alter the structure of the plastic. Radical formation was studied using electron paramagnetic resonance (EPR) spectroscopy in six plastic scintillator types of either polystyrene (PS) or polyvinyl toluene (PVT) base, and computational EPR studies were conducted on two small monomer structures and two large polymer, plastic-like computer models. Damage was simulated in the computational models by removing an increasing number of hydrogen atoms. Plastic samples, of volume 500 ⇥500 ⇥ 250 µm, were to subjected protons accelerated to 6 MeV using the tandem accelerator at iThemba LABS, Gauteng, to increasing target doses of 0.8 MGy, 2.5 MGy, 8.0 MGy, 25 MGy, 50 MGy, and 80 MGy. The experimental EPR data taken after two weeks of the sample exposure to air indicate the presence of peroxy-type radicals that initiate chemical reactions, discolour the plastic, and decrease the eﬃciency of the plastic. Furthermore, the data suggests that damaged PS and PVT samples are susceptible to diﬀerent mechanisms of radiation damage. However, results pertaining to the decrease in the g-factor and the increase in normalised EPR intensity suggest that all plastics behave similarly using an EPR analysis as a function of dose. Thus, the EPR analysis could not identify a speciﬁc plastic that would perform better than the existing plastics used in the TileCal. The computational chemical potential results indicate that electron transfer between damaged pristine and damaged models is possible. In the two small damaged models, the computational EPR data indicate the presence of a various stable akyl-like radicals depending on the site from which the hydrogen atoms are removed. In the two large damaged models, these results indicate a number of alkyl-, benzyl-, and cyclohexadienyl-like radicals.
A dissertation submitted to the Faulty of Science, University of the Witwatersrand, Johannesburg, in fulﬁlment of the requirements for the degree of Master of Science. April 2017.
Keywords: Particle accelerators; Large Hadron Collider (France and Switzerland); Calorimeter; Scintillators